2021
DOI: 10.1108/mbr-02-2020-0034
|View full text |Cite
|
Sign up to set email alerts
|

Political animosity in cross-border acquisitions: EMNCs’ market and nonmarket strategy in a developed market

Abstract: Purpose Many multinational corporations that originate from emerging economies (emerging market multinational corporations (EMNCs)) opt for acquiring a target firm in a developed market to expediently upgrade their strategic capabilities. To successfully achieve their strategic goals in the developed markets, EMNCs may use market actions and nonmarket actions to mitigate the potential risk derived from the national political differences between their home emerging economy and host developed economy. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 105 publications
0
29
0
Order By: Relevance
“…We empirically demonstrate that intermittent natural disasters risk represents a relevant threat that reduces the likelihood of success whereas rule of law has no significant effect. In doing so, we point to the importance of the distinction between exogenous and endogenous risks, as the former are fully out of the control of the firm, whereas the latter can be, to some extent, controlled and shaped through corporate political action and lobbying (Hillman and Hitt, 1999;Hillman et al, 2004;Liou et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We empirically demonstrate that intermittent natural disasters risk represents a relevant threat that reduces the likelihood of success whereas rule of law has no significant effect. In doing so, we point to the importance of the distinction between exogenous and endogenous risks, as the former are fully out of the control of the firm, whereas the latter can be, to some extent, controlled and shaped through corporate political action and lobbying (Hillman and Hitt, 1999;Hillman et al, 2004;Liou et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…While firms have little or no influence on the sources of exogenous risk, they might have some control on the sources of endogenous risk, individually or in association with other firms, by developing political capabilities such as negotiation and lobbying skills, personal ties and connections with politicians, campaign contributions, political coalitions, etc. (Hillman and Hitt, 1999;Henisz, 2003;Hillman et al, 2004;Jiménez, 2010;Liou et al, 2021). This is particularly the case in highly regulated sectors such as the infrastructure sectors (García-Canal and Guillén, 2008;Holburn and Zelner, 2010;Jiménez et al, 2014;Fern andez-Méndez et al, 2015) and the natural resources sector (Lupton et al, 2021), where given the salient policy issues under administrative consideration, firms tend to get involved in political actions (Buchholz, 1990;Vogel, 1996;Bonardi and Keim, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers generally study CPA in isolation from other market actions of the organization, but recently researchers have identified that managers engage in nonmarket activity in combination with market actions in an effort to increase performance (Funk and Hirschman, 2017; Ahammad et al , 2017; Liou et al , 2021). In continuing the research investigating CPA as an approach used in conjunction with other market-based strategies, we examine the interplay in human capital and political activity.…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%